Exploring the relationship between employee engagement and counterproductive work behaviour - Sphindile Mvuyana; Thokozani Ian Nzimakwe; Reward Utete (Frontiers in Psychology)
IntroductionDespite the cumulative increase in counterproductive work behaviour in various organisations which have ripple effects on general organisational performance, little is known on how employee engagement relates to counterproductive work behaviour. The purpose of the study was to explore the relationship between employee engagement and counterproductive work behaviours of employees at the leading university in South Africa.MethodsThe study employed qualitative approach and structured interviews were used to gather data from the both academic and professional services staff. The collected data from fifteen (15) respondents were analysed using thematic analysis, leading to the identification of key themes and patterns.ResultsBased on the findings, it became evident that there is an inverse relationship between employee engagement and counterproductive work behaviour. The study also revealed lack of an effective probationary period, unequal treatment of academic and professional services staff in terms of retention strategies, and insufficient attention given to employee engagement were among the primary factors contributing to disengagement within the institution.DiscussionThe study concluded that there is a pressing need for change and the implementation of new systems to enhance employee engagement at the organisation. Management should also establish a probationary period for new employees, providing sufficient time for them to acclimate to their roles and allowing line managers and HR to identify and address training needs. Management should enhance communication and feedback channels between employees and management to foster a sense of inclusiveness and ensure that employee concerns are heard and addressed.